Data Hiding Through Media Audio - Sumi Khairani (Program Studi Sistem Informasi, 2017)
Audio watermarking can use with various ways. Firstly, it have used for proving of ownership, production of information, copyright information in a form of a watermark, and it have routed directly in the recording. Specific owners have different insertion information. It can also be used for controlling access, watermark becomes a trigger to play music. Keeping track of unauthorized copies is a very important application. Personal information have inserted into the music. It used as numbers for customers to discover music.